Considerations for rules of origin under the African Continental Free Trade Area - Landry Signé; Payce Madden (Journal of African Trade, 2021)
Rules of origin are used to determine a product's eligibility for preferential tariffs under a free trade agreement and have major implications for the extent of trade under the agreement and the growth of regional value chains. Firms choose to comply with rules of origin when the benefits of trading under an agreement, determined primarily by the preference margin, are higher than the costs of complying with rules of origin, determined by the costs of sourcing products from within the free trade area and from the costs of certifying that products comply with rules of origin. In addition, as there is a fixed cost component of complying with rules of origin, compliance is more likely when trade volumes are large. Negotiations for rules of origin under the African Continental Free Trade Area (AfCFTA) are complicated by the diverse rules of origins used in Africa's many regional economic communities. We analyze preference margins, the availability of intermediate inputs, trade volumes, and potential certification costs in Africa. We find that although preference margins are high for many products, the availability of intermediate inputs and trade volumes are generally low, and certification may be difficult for Africa's large numbers of small and mid-size enterprises. We then argue that the AfCFTA should pursue progressive harmonization of regional economic communities' rules of origin across the continent, with the goal of gradually reducing the number of product-specific rules and moving towards the overarching application of general, co-equal rules. In addition, the costs of certification must be minimized in order to increase exporter participation
Keywords: 330; Rules of origin; African continental free trade agreement; preferential trade agreements; intra-African trade